Manufacturing of nanocomposite structural ceramic materials and coatings. (26th May 2009) - Gadow, R.; Kern, F.; Killinger, A.
So far research on ceramic nanocomposites was focused on materials science aspects neglecting the development of suitable manufacturing technologies. The high performance properties of nanocomposites make final machining unaffordable. Near-net-shape manufacturing is mandatory to accomplish cost targets. Feedstocks with tailored micro-nano architecture can fulfil these requirements, using homogeneously dispersed nanosized powders in a matrix of sub-micron sized grains. Nanoceramic coatings deposited by thermokinetic deposition processes open new prospects and applications in surface technology. The novel HVSFS-process permits direct spraying of liquid nanodispersions in a HVOF torch yielding ultradense and thin oxide and cermet coatings for automotive, aerospace and mechanical engineering.